STAR Quartet Card Learning Media Improves Social Science Learning Outcomes Human Motion Joint Material Class VI - Luvensia Mei Fajri; Deasylina da Ary (CV. Creative Tugu Pena, 2025)
effectiveness of the Joint & Motion Quartet Card (STAR) Learning media on student learning outcomes in human motion joint material in science subjects. This study applies a Research and Development (R&D) approach using the ADDIE development model. The participants in this research include material experts and media experts, while the trial was conducted with 26 sixth-grade students at SD N Mangkangwetan 03, Semarang City. This media contains visualizations of human motion joints which are visual stimuli for students to create movements creatively, so that students can find the characteristics of human motion joints. The results indicated that the material feasibility achieved a score of 68 with a percentage of 86%, categorized as very feasible. Meanwhile, the media feasibility reached a score of 76 with a percentage of 95%, also classified as highly appropriate for implementation in the learning process. Furthermore, the analysis revealed an improvement in student learning outcomes, as the posttest scores exceeded the pretest scores. The effectiveness test results demonstrated a significant difference between pre-test and post-test scores (Sig. 0.002 < 0.05), with an N-Gain value of 0.5870, which falls into the moderate category. Thus, the Joint & Dance Quartet Card (STAR) media can be used as an innovative learning medium to improve students' learning outcomes on human motion joint materials in elementary school.